Essential Role of Electrode Materials in Electrochemiluminescence Applications. Issue 12 (25th November 2016) - Valenti, Giovanni; Fiorani, Andrea; Li, Haidong; Sojic, Neso; Paolucci, Francesco
Abstract: The phenomenon of electrochemiluminescence (ECL) is luminescence triggered by electrochemical reactions at electrodes. Heterogeneous electron transfers are deeply dependent on electrode materials, therefore, besides the usual parameters, the right choice of the electrode is a crucial point to address properly in order to maximize the emission efficiency. Many different electrodes have been studied, from metallic platinum or gold through transparent indium‐doped tin oxide to carbon‐based electrodes, and others, such as paper‐based and boron‐doped diamond. This review summarizes results of ECL at different electrode surfaces, disclosing the relative advantages and disadvantages, with a particular attention to the reference Ru(bpy)3 2+ /TPrA coreactant system. In other words, we offer an insight to recognize and select the optimal electrode material for the ECL systems of interest with particular emphasis on the biosensing applications. Abstract : Do the right thing : The role of different electrode materials in electrochemiluminescence is critically reviewed, compared, and advantages and disavantages evaluated. The purpose is to offer guidelines for users to choose the best electrode material for the electrochemiluminescence systems of interest.